SYSTEMATIC REVIEW : Hubungan Genetik dengan Stunting pada Balita - Heriawita, Heriawita; Sulastri, Delmi (Jurnal Ners, 2024)
Stunting is a conditioning in which toddlers have less length or height compared to their age. The occurrence of stunting is influenced by many factors. Mothers height is a very important factor, because of the short chromosome carried by the mother. The incidence of stunting in toodlers who have short mothers (<150 cm) will be exacerbated if other factors are ignored. The aim of study is to identify a genetic relationship with stunting. This study uses a systematic review method. Systematic review is carried out by identifying national journals and international journals. Search for library sources in this article through the Google Scholar, Pub Med, Science Direct database for 2019-2023. From this study it is known that there is a relationship between genetics and stunting. However, stunting is more often caused by a complex interaction between genetic and environmental factors, including inadequate nutritional intake. According to Blum (1974) genetic factors affect the health status 5%. Although a child’s height is influenced by the the genetic factors of their parents, nutritional and environmental factors play an important role in preventing stunting. It is important for parents to apply the behaviour of providing good nutrition, a healthy environment, as well as proper care and stimulation to ensure that children can grow and develop optimally, to prevent stunting in toddlers.